Transboundary Externalities and Property Rights: An International River Pollution Model - Gerard van der Laan; Nigel Moes (Tinbergen Institute, 2012)
In this paper we study international river pollution problems. We introduce a model in which the agents (countries) located along a river derive benefit while causing pollution, but also incur environmental costs of experiencing pollution from all upstream agents. We find that total pollution in the model decreases when the agents decide to cooperate. The resulting gain in social welfare can be distributed among the agents based on the property rights over the river. Using principles from international water law we suggest 'fair' ways of distributing the property rights and therefore the cooperative gain.
urn:NBN:nl:ui:31-1871/38493
Keywords: C70; D60; Q53; 330; international river; pollution; externality; property rights; value; Fluss; Gewässerbelastung; Eigentumsrecht; Umweltschutz; Spieltheorie